PERANCANGAN SISTEM INFORMASI AKUNTANSI PEMBELIAN BAHAN BAKU (Studi Kasus : PT. DCM (DADALI CITRA MANDIRI) BANDUNG) - Apriani Puti Purfini; Teguh Prasetyo; S Supriyati (@is The Best : Accounting Information Systems and Information Technology Business Enterprise, 2012)
PT DCM (Dadali Citra Mandiri) is manufacturing business which is active in service of telecommunications and construction. Research done at Staff Purchasing, concerning Information System of Accountancy of Raw Material Purchasing. System which walk in company not yet computerized full, and informsai yielded by not yet as according to accountancy standard going into effect in Indonesia. Writer take the title " Design Information System of Accountancy Purchasing Raw Material At PT. Dadali Citra Mandiri Bandung". Desain Research which writer use is descriptive desain research and also desain research with the data of primary and sekunder, research type used is academic research, data type used is data qualitative and quantitative data, research method used is descriptive research method, and research method with an eye to evaluatif, technique of data collecting used is field study and book study, method of system development used is methodologies orienting at output, process and data. Structure of system development used by is Waterfall. System development of Information used is context diagram, data flow diagram, and flowchart. Design Information System of Accountancy Purchasing Raw Material done for make system better, yielded information as according to accounting standard like Receivable card, aging receivable, and receivable report, and especial report like income statement and balance sheet.